2014
DOI: 10.7860/jcdr/2014/8825.4561
|View full text |Cite
|
Sign up to set email alerts
|

Ethics Workshops-Are They Effective in Improving the Competencies of Faculty and Postgraduates?

Abstract: Introduction: Responsible conduct of research requires a good knowledge about research ethics. With the recent changes in the clinical trial regulations and the proposed introduction of ethics in medical curriculum by the Medical Council of India, there is an urgent need to train the medical faculty and postgraduates in research ethics. Methodology:We wanted to measure the effectiveness of a one day program which was organized using didactic lectures and case scenarios on the knowledge, attitude and skills on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…Notably, only 27.4% of clinical trials reported that written consent had been obtained, and only 1.0% of clinical trials included the ethics committee reference number. Despite the rate of ethical approval reporting improved sharply between 2013 and 2016 (all p < 0.001) which may be induced by various kinds of efforts like the “Joint Statement of Establishing a Chinese Clinical Trial Registration and Publishing System,” 45 the regulation of ethics committee, as well as the effectiveness of many ethics workshops, 46 these data symbolize that the publication of ethically uncertain research occurs commonly in nursing journals in China. Most of the nursing periodicals in China did not meet their commitment to the Declaration of Helsinki which stated, “Publishers have ethical obligations”; significantly, the Declaration of Helsinki clearly stated that “reports of experimentation not in accordance with the principles laid down in this Declaration should not be accepted for publication.” Although a waiver of informed consent could be allowed in some special circumstances by the ethical guideline of the IRB or Council of Europe and Council for International Organizations of Medical Sciences (CIOMS), there were no descriptions of impediments to obtaining written informed consent in these retrieved clinical trials in the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, only 27.4% of clinical trials reported that written consent had been obtained, and only 1.0% of clinical trials included the ethics committee reference number. Despite the rate of ethical approval reporting improved sharply between 2013 and 2016 (all p < 0.001) which may be induced by various kinds of efforts like the “Joint Statement of Establishing a Chinese Clinical Trial Registration and Publishing System,” 45 the regulation of ethics committee, as well as the effectiveness of many ethics workshops, 46 these data symbolize that the publication of ethically uncertain research occurs commonly in nursing journals in China. Most of the nursing periodicals in China did not meet their commitment to the Declaration of Helsinki which stated, “Publishers have ethical obligations”; significantly, the Declaration of Helsinki clearly stated that “reports of experimentation not in accordance with the principles laid down in this Declaration should not be accepted for publication.” Although a waiver of informed consent could be allowed in some special circumstances by the ethical guideline of the IRB or Council of Europe and Council for International Organizations of Medical Sciences (CIOMS), there were no descriptions of impediments to obtaining written informed consent in these retrieved clinical trials in the studies included in this review.…”
Section: Discussionmentioning
confidence: 99%
“…Combining small group learning, practical cases, role-play and interdisciplinary learning have also been reported as effective approaches to providing education in research ethics (Zawati et al 2015). Similarly, programs reported to improve capacity in research supervision have included short courses, workshops or specific training (Balster et al 2010;Ramalingam et al 2014;Ajuwon and Kass 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is great variation in the timing and duration of such training sessions. Formal teaching run by the host organisation or institution tended to come in the form of mandatory training programmes [80,81] that span the course of a few years [62,82] or a single day [67]. Some programs are held over a few hours each year [58,94], or each month or every few months as part of a wider residency training program [49,59,83].…”
Section: Pedagogymentioning
confidence: 99%